Dispensação de Oseltamivir no Município de Passo Fundo - RS - Gilberto Santetti; Anderson Flores (Universidade de Santa Cruz do Sul, 2012)
The knowledge of theuser profile of the antiviral oseltamivir (Tamiflu) can resultin benefits to develop prevention actions and strategiesand more effective treatment against influenza and itscomplications. In this way, the objective of this study was toevaluate the user profile of the antiviral (Oseltamivir) in thecity of Passo Fundo, RS. Methods: Descriptive research ofquantitative and exploratory approach based on the analysisof forms used for dispensing oseltamivir to human Influenzacases treated at the city of Passo Fundo, between the 25thand 35th Epidemiological Week in the year 2011. Results:50% were females, and only one of them one was pregnant(25th week of gestation). The most affected age group was20 to 29 years, with 25.5% of cases, followed by 30 to 39years, with 18.9%. Only 25 individuals (27.8% of cases) hadbeen vaccinated in that year. The most common symptomswere fever, coughing, headache, myalgia, sore throat, chillsand runny nose and the most recurrent comorbidity waschronic lung disease. Conclusion: Winter results in anincreased occurrence of respiratory diseases, often requiringthe use of oseltamivir. It is necessary to discuss issuesrelated to National Vaccination Campaign this year, which,among the priority groups, did not include the young adultpopulation, considering that is the most affected age range.It is also necessary to emphasize the careful filling out ofthe information in the dispensing form, which could improvethe analysis of more consistent data.